Analisis Problematika Pembelajaran Bahasa Arab Kelas Sistem Kredit Semester (SKS) di MAN 2 Yogyakarta Tahun Ajaran 2022–2023 - Afiyah Hasbiyallah; Nurul Huda (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
Arabic language learning in Semester Credit System (SKS) class, where both students and teachers are pressed for time and curriculum demands, inevitably encounters various problems, both linguistic and non-linguistic, during the learning process. Based on this, the focus of this study includes the challenges in Arabic language learning within SKS class, as well as the efforts made by teachers to overcome these challenges in SKS class at MAN 2 Yogyakarta. This research is a descriptive qualitative study employing four data collection methods: observation, interviews, questionnaires, and documentation. The results of the study show the following: First, the linguistic problems found include issues related to phonology, word formation (morphology), sentence structure (syntax), meaning (semantics), and writing system (orthography). Meanwhile, the non-linguistic problems identified include students’ diverse backgrounds, low learning motivation, unattractive textbook design, limited instructional time, and an unsupportive language environment. Second, the efforts made by teachers to address these challenges include visualizing vocabulary, encouraging practical use of the given vocabulary, providing basic Imla’ (dictation) training at the beginning of the semester, and creating a more relaxed and non-intimidating classroom atmosphere.